Problem of vitamin D deficiency - Зафт, В. Б.; Рыкова, О. В.; Зафт, А. А.; Клімова, Ж. О.; Бойко, І. В.; Галицька, В. В. (REPRODUCTIVE ENDOCRINOLOGY, 2015)
In the article the problem of vitamin D deficiency, and its significance for the human body are presented. Its main source is fortified foods and dietary supplements. Vitamin D is also produced in the body by the action on the skin of ultraviolet radiation. Low concentrations of vitamin associated with level of total mortality, cardiovascular diseases and cancer. It is proven protective effects of vitamin D in diseases of the skeletal system (rickets, osteoporosis, osteomalacia). Modern laboratory methods for diagnosis of deficiency of vitamin D, which are used in the laboratory of “Synevo Ukraine”, are presents.